Mulleres galegas e emigración transatlántica: De Mamasunción a Dúas letras (ou de como a figura da nai toma a palabra) - Sánchez, Mariela Paula (2021)
This article proposes to analyse the representation of women in two short films that focus on emigration from Galicia to Latin America, with an emphasis on the perspective of mothers who remain in their home village awaiting transatlantic news. The objective is to address the treatment of themes such as loneliness, communication problems and the prejudices related to the image of women in the pioneering classic Mamasunción by Chano Piñeiro (1984) and in Dúas letras by Fina Casalderrey and Eloy Varela (2011). In fact, Dúas letras is, in a way, a remake of Piñeiro’s inaugural film but with a different perspective, especially by providing the mother with a voice. The aim is to discuss certain clichés of inaction and mere ‘Penelopian’ expectations that are generally associated with the images of waiting that predominate in these productions. Despite the isolation to which they are subjected and the fact that they are not involved in any emigration, the women in question are key to understanding the migratory process and some of its features: the lack of formal education, economic needs, secrecy, simulation; but also manifestations of solidarity that change the focus of the story and the interactions between its characters. We will consider specific bibliography that will allow us to investigate women’s subaltern condition, to study the alternate involvement of body language, orality and writing, and the means of connection —and the lack of encounter— between different latitudes, generations and genres through the epistolary medium for those who are left at the mercy of news from others that arrive and are decoded with extreme difficulty and mediation.